The presence of structuralist learning theory in the Arabic language textbook for the fourth year of middle school - benketaf, amina; fassi, omar (El Omda in Linguistics and Discourse Analysis, 2025)
Structural theory helps teachers develop effective teaching strategies based on a deep understanding of the basic structure of language, which leads to improved language acquisition among pupils. The applied study aims to show the presence of structural theory and its methods in preparing and presenting Arabic language lessons through the analysis of the Arabic language textbook in the fourth year of middle school based on the descriptive analytical approach. The results of the study showed that structural theory elevates pupils by creating a solid curriculum, teaching pupils problem-solving skills, and enhancing their language proficiency. the textbook emphasizes the importance of active learning centered on building the pupil self-learning.